Library Services and Availability of Information Resources in University Libraries, South-South Nigeria - Patience Owere Ekpang; Martina Ekpenyong Ekeng (PINISI Discretion Review, 2021)
This study investigated the relationship between library services and the availability of information resources in federal university libraries, in South-South, Nigeria. To achieve the purpose of this study, two research questions were raised and two hypotheses were formulated to guide the study. The ex-post facto research design was adopted for the study. The population of the study was 16620 students and a sample of 800 respondents was selected for the study. The selection was done through the stratified and purposive random sampling technique. The results of the analyses revealed a significant relationship between user education and preservation of information resources and availability of information resources. Based on these findings, it was recommended, among others that: User education should be adequately given to students to enable them to make the most use of the information resources and Government should prioritize funding for the preservation of information resources for university libraries.